2020
DOI: 10.1590/0034-7167-2017-0853
|View full text |Cite
|
Sign up to set email alerts
|

Multiprofessional team perception of a music therapeutic workshop developed by nurses

Abstract: Objective: To understand the perception of a multiprofessional team regarding the use of music in a therapeutic workshop developed by nurses. Method: Qualitative study, of the exploratory type. Data were collected through semi-structured interviews, with the participation of 13 professionals from a Psychosocial Care Center in a municipality of Minas Gerais’ Zona da Mata, and analyzed according to Michel Maffesoli’s comprehensive sociology approach. Results: The testimonies revealed that the use of music in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
0
0
2
Order By: Relevance
“…The findings in our current work were very similar, with the participants describing their opinions that MT allows both enjoyment and the expression of feelings in healthcare personnel and patients alike, perhaps also impacting recovery and increasing social engagement in their relationships with patients, thereby improving affective ties. There are also examples of studies carried out in adults in mental health units which support the results of the aforementioned studies (Marques et al, 2020;Silverman & Bibb, 2018). These showed that MT reduced agitation and motivated and activated communication channels, thereby facilitating the evocation of memories, feelings, and emotions in patients.…”
Section: The Benefits Of Music Therapy In Patients: Children and Adol...supporting
confidence: 57%
“…The findings in our current work were very similar, with the participants describing their opinions that MT allows both enjoyment and the expression of feelings in healthcare personnel and patients alike, perhaps also impacting recovery and increasing social engagement in their relationships with patients, thereby improving affective ties. There are also examples of studies carried out in adults in mental health units which support the results of the aforementioned studies (Marques et al, 2020;Silverman & Bibb, 2018). These showed that MT reduced agitation and motivated and activated communication channels, thereby facilitating the evocation of memories, feelings, and emotions in patients.…”
Section: The Benefits Of Music Therapy In Patients: Children and Adol...supporting
confidence: 57%
“…A visita musical em questão mostrou seu alinhamento com o cuidado transpessoal ao proporcionar bem-estar para o corpo, para a mente e para a alma/espírito, na percepção dos participantes. Além disso, por meio dessa atividade, os egressos enxergaram a música como instrumento de humanização da assistência, e, por meio dela, aproximaram-se dos cuidados, conhecendo melhor suas necessidades integrais (Marques;Alves;Carbogim et al, 2020).…”
Section: Discussionunclassified
“…Assim sendo, o cuidado musical tem a natureza de contrapor as práticas convencionais e tecnicistas produzidas pelo ambiente hospitalar, por meio das letras e melodias que tocam o coração e a alma dos pacientes e seus familiares. Frente a essa realidade, o cuidado é produzido considerando a história e experiências humanas, e, a partir disso, cria condutas terapêuticas para ressignificar o olhar do ser cuidado e do cuidador (Marques;Alves;Carbogim et al, 2020).…”
Section: Discussionunclassified
“…Ressalta-se que as atividades em grupo são citadas em outras pesquisas como fator motivador para a permanência no serviço e adesão ao tratamento (7) . Existe também a necessidade de que essas atividades passem por uma ressignificação, a partir de uma linha de cuidados que favoreça a subjetividade do usuário do serviço, através da utilização de recursos inovadores que correspondam às recomendações do movimento de Reforma Psiquiátrica (13) .…”
Section: Discussionunclassified